2010
DOI: 10.1371/journal.ppat.1000947
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of PD-1, 2B4, CD160 and KLRG1 on Exhausted HCV-Specific CD8+ T Cells Is Linked to Antigen Recognition and T Cell Differentiation

Abstract: Exhausted CD8+ T cell responses during chronic viral infections are defined by a complex expression pattern of inhibitory receptors. However, very little information is currently available about the coexpression patterns of these receptors on human virus-specific CD8+ T cells and their correlation with antiviral functions, T cell differentiation and antigen recognition. We addressed these important aspects in a cohort of 38 chronically HCV infected patients and found a coexpression of inhibitory receptors such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
340
2
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 332 publications
(382 citation statements)
references
References 40 publications
23
340
2
8
Order By: Relevance
“…Activation and effector functions of T cells are regulated by CD3/T-cell receptor (TCR) signal upon antigenic engagement and by a group of signals from costimulatory molecules, including CD28, cytotoxic T-lymphocyte-associated protein 4 (CTLA4), inducible T-cell costimulator (ICOS), programmed death-1 (PD-1), T cell immunoglobulin mucin-3 (Tim-3), and CD244 (2B4) (9)(10)(11)(12)(13)(14). Accumulating evidence suggests that a variety of pathogens, including HIV, simian immunodeficiency virus, hepatitis C virus (HCV), lymphocytic choriomeningitis virus, and Plasmodium, induce immune evasion by up-regulating costimulatory molecules such as PD-1, CTLA4, and Tim-3 as a result of repeated antigenic stimulation of T cells.…”
Section: T Uberculosis (Tb) Caused By Mycobacterium Tuberculosis (Mtb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Activation and effector functions of T cells are regulated by CD3/T-cell receptor (TCR) signal upon antigenic engagement and by a group of signals from costimulatory molecules, including CD28, cytotoxic T-lymphocyte-associated protein 4 (CTLA4), inducible T-cell costimulator (ICOS), programmed death-1 (PD-1), T cell immunoglobulin mucin-3 (Tim-3), and CD244 (2B4) (9)(10)(11)(12)(13)(14). Accumulating evidence suggests that a variety of pathogens, including HIV, simian immunodeficiency virus, hepatitis C virus (HCV), lymphocytic choriomeningitis virus, and Plasmodium, induce immune evasion by up-regulating costimulatory molecules such as PD-1, CTLA4, and Tim-3 as a result of repeated antigenic stimulation of T cells.…”
Section: T Uberculosis (Tb) Caused By Mycobacterium Tuberculosis (Mtb)mentioning
confidence: 99%
“…It has recently been shown that CD244 is expressed on virus-specific CD8 + T cells (9,(39)(40)(41) and that CD244 signaling correlates with viral persistence of hepatitis B virus (HBV) and HCV in humans (9,39,40). However, little is known about the molecular mechanism and consequence for CD244 regulation of T-cell effector functions during active TB infection.…”
Section: T Uberculosis (Tb) Caused By Mycobacterium Tuberculosis (Mtb)mentioning
confidence: 99%
“…The results of recent studies demonstrate that the stage of Ag-specific CD8 + T cell dysfunction correlates with a progressive increase in the amount and diversity of inhibitory receptors expressed and coexpressed on these cells. These receptors include programmed cell death-1 (PD-1), CTLA-4/CD152, T cell Ig mucin-3 (TIM-3), and CD160 and CD244 (2B4) (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Vascularized heart grafts from bm12 donor mice were transplanted heterotopically, using a standard microsurgical technique, in C57BL/6 WT or was administered i.p., 0.5 mg on day 10 and 0.25 mg on day 12 and day 14 PT or 0.5 mg on day 14 and 0.25 mg on days 16,18,20,22 Isolation of GIL. Cardiac grafts were harvested at the designated time points, incubated at 37°C with collagenase-II/DNase I mixture for 20 min, then passed gently through a 40-μm filter (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…S7 and S8). Coexpression of inhibitory receptors with low expression of CD127 correlates with impaired proliferative capacity (22), and impaired proliferative potential is a key feature of T-cell exhaustion. Using Ki67 as a marker of proliferation, we noted that a significantly lower proportion of CD4 T cells from Fut7 −/− recipients were proliferating in vivo in response to alloantigen encounter after transplantation compared with those from WT recipients (8.37% ± 0.8% vs. 11.1% ± 0.4%, P < 0.04; Fig.…”
Section: Impaired Selectin-dependent Leukocyte Recruitment Leads To Cmentioning
confidence: 99%